2023
DOI: 10.1002/jat.4499
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of selenium nanoparticles in laboratory animals: A review

Abstract: This paper provides a comprehensive summary of the main toxicological studies conducted on selenium nanoparticles (NPs) using laboratory animals, up until February 28, 2023. A literature search revealed 17 articles describing experimental studies conducted on warm‐blooded animals. Despite some uncertainties, in vivo studies have demonstrated that selenium NPs have an adverse effect on laboratory animals, as evidenced by several indicators of general toxic action. These effects include reductions of body mass, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 92 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…Kidneys play an important role in selenium homeostasis [ 41 , 52 ]. Selenium is often used as a protector against nephrotoxic effects of chemicals (e.g., [ 53 , 54 , 55 , 56 , 57 ]). However, it has been shown that rising doses of Se NPs have an increasingly pronounced nephrotoxic effect and accumulate in renal tissues [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys play an important role in selenium homeostasis [ 41 , 52 ]. Selenium is often used as a protector against nephrotoxic effects of chemicals (e.g., [ 53 , 54 , 55 , 56 , 57 ]). However, it has been shown that rising doses of Se NPs have an increasingly pronounced nephrotoxic effect and accumulate in renal tissues [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to high levels of Se for a long time, it can cause toxic reactions including congenital disability, reproductive disorders, liver failure, skin damage, respiratory failure, and hair and nail loss [ [42] , [43] , [44] , [45] , [46] ]. For animals, excessive Se intake can lead to various negative effects, including weight loss [ 47 , 48 ], impaired growth [ 49 ], Se accumulation and cellular damage in liver tissue [ 50 , 51 ], localized hair loss [ 52 ], impairment of fatty acid, protein, and carbohydrate metabolism, as well as destructive changes in the intestines [ 50 , 53 ]. High Se concentration also has a toxic effect on plant growth and physiological activities [ [54] , [55] , [56] , [57] ], including yellowing of leaves, stunted growth, and reduced biomass [ 1 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%